2012
DOI: 10.1002/jhet.850
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic N‐Heterocyclic Compounds, Part 72: Reaction of N‐([1]Benzofuro (or Benzothieno)[3,2‐d]pyrimidin‐4‐yl)formamidine and N‐(Pyrido[2,3‐d]pyrimidin‐4‐yl)formamidine Derivatives with Hydroxylamine Hydrochloride

Abstract: The reactions of N‐([1]benzofuro[3,2‐d]pyrimidin‐4‐yl)formamidines with hydroxylamine hydrochloride gave rearranged cyclization products via ring cleavage of the pyrimidine component accompanied by a ring closure of the 1,2,4‐oxadiazole to give N‐[2‐([1,2,4]oxadiazol‐5‐yl)[1]benzofuran‐3‐yl)formamide oximes. N‐([1]Benzothieno[3,2‐d]pyrimidin‐4‐yl)formamidines and N‐(pyrido[2,3‐d]pyrimidin‐4‐yl)formamidines with hydroxylamine hydrochloride gave similar results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…We also reported that some of the products ( 1 ) showed significant inhibitory effects on the formation of pentosidine, which is one of the representatives of advanced glycation end products . Recognizing that other fused aromatic derivatives in addition to quinazolines should be susceptible to this transformation , we decided to explore reactions of hydroxylamine hydrochloride with pyrido[3′,2′:4,5]thieno[3,2‐ d ]pyrimidines and pyrido[2′,3′:4,5]furo[3,2‐ d ]pyrimidines as an approach to potential pharmaceutics. These are aza‐analogs of benzofuro[3,2‐ d ]pyrimidines and benzothieno[3,2‐ d ]pyrimidines , products of rearrangement from which also showed some inhibitory effects on pentosidine formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also reported that some of the products ( 1 ) showed significant inhibitory effects on the formation of pentosidine, which is one of the representatives of advanced glycation end products . Recognizing that other fused aromatic derivatives in addition to quinazolines should be susceptible to this transformation , we decided to explore reactions of hydroxylamine hydrochloride with pyrido[3′,2′:4,5]thieno[3,2‐ d ]pyrimidines and pyrido[2′,3′:4,5]furo[3,2‐ d ]pyrimidines as an approach to potential pharmaceutics. These are aza‐analogs of benzofuro[3,2‐ d ]pyrimidines and benzothieno[3,2‐ d ]pyrimidines , products of rearrangement from which also showed some inhibitory effects on pentosidine formation.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing that other fused aromatic derivatives in addition to quinazolines should be susceptible to this transformation , we decided to explore reactions of hydroxylamine hydrochloride with pyrido[3′,2′:4,5]thieno[3,2‐ d ]pyrimidines and pyrido[2′,3′:4,5]furo[3,2‐ d ]pyrimidines as an approach to potential pharmaceutics. These are aza‐analogs of benzofuro[3,2‐ d ]pyrimidines and benzothieno[3,2‐ d ]pyrimidines , products of rearrangement from which also showed some inhibitory effects on pentosidine formation. Here, we report in detail the results of our present investigation.…”
Section: Introductionmentioning
confidence: 99%